2020
DOI: 10.1007/s12630-020-01727-z
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation for respiratory failure in COVID-19 patients: outcome and time-course of clinical and biological parameters

Abstract: z) contains supplementary material, which is available to authorized users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 10 publications
2
15
0
5
Order By: Relevance
“…Our results T A B L E 4 Demographic, biological, ventilatory, hemodynamic, and therapeutic parameters in survivors and non-survivors of the patients implanted with VV-ECMO show a transient drop in the lymphocyte count the day after ECMO insertion, with a return to normal values at day 3. This result is consistent with the results published in a case series of 12 ECMO COVID-19 patients showing the same results (Huette et al, 2020). However, the authors found that most severe COVID-19 cases had persistently low lymphocyte counts, which our study failed to show.…”
Section: Post-intubationsupporting
confidence: 94%
“…Our results T A B L E 4 Demographic, biological, ventilatory, hemodynamic, and therapeutic parameters in survivors and non-survivors of the patients implanted with VV-ECMO show a transient drop in the lymphocyte count the day after ECMO insertion, with a return to normal values at day 3. This result is consistent with the results published in a case series of 12 ECMO COVID-19 patients showing the same results (Huette et al, 2020). However, the authors found that most severe COVID-19 cases had persistently low lymphocyte counts, which our study failed to show.…”
Section: Post-intubationsupporting
confidence: 94%
“…Similar to the subsequent positive reports that demonstrated the effectiveness of V-V ECMO in COVID-19 associated pneumonia. [17][18][19] In this study, the presence of lower PaO 2 /FiO 2 ratio, lower C RS , and high driving pressure is consistent with previously described pathophysiology of COVID-19 pneumonia. 20 Previous studies have confirmed the association of lower C RS as well as high driving pressure with poor outcome.…”
Section: Discussionsupporting
confidence: 91%
“…Zeng et al [ 22 ] reported 12 critically ill patients requiring ECMO, where half of them died from septic shock and multi-organ failure. However, Huette et al [ 23 ] reported outcomes from 12 patients on ECMO where 10 of 12 patients were weaned from ECMO, 9 patients were weaned from mechanical ventilation, and 8 patients were discharged from the hospital. Patients weaned from ECMO demonstrated an increase in their lymphocyte count and a decrease in their fibrinogen levels[ 23 ].…”
Section: Special Considerations For Ecmo Use In Covid-19 Patientsmentioning
confidence: 99%
“…However, Huette et al [ 23 ] reported outcomes from 12 patients on ECMO where 10 of 12 patients were weaned from ECMO, 9 patients were weaned from mechanical ventilation, and 8 patients were discharged from the hospital. Patients weaned from ECMO demonstrated an increase in their lymphocyte count and a decrease in their fibrinogen levels[ 23 ]. There was also an increase in the PaO 2 /FiO 2 ratio in these patients[ 23 ].…”
Section: Special Considerations For Ecmo Use In Covid-19 Patientsmentioning
confidence: 99%
See 1 more Smart Citation